Role of Unani Polyherbal Formulations in the Treatment of Diseases with Special Reference to Neurodegenerative Disorders - Siddique, Yasir H. (CNS & Neurological Disorders - Drug Targets, 2023)
Unani system of medicine is based on the use of natural plant products. Unani polyherbal formulations (UPFs) are being prescribed for the treatment of various ailments. The preparations of the UPFs also required the animal products such as honey and umber. UPFs have been reported to cure various diseases but still lack scientific credibility. The Unani system is based on the holistic approach; the synergistic role of the compounds has been suggested to play a protective role against the illness. The present review has compiled the studies carried out on UPFs used to treat various diseases with special reference to neurodegenerative ailments. The exorbitant cost of conventional treatment has led the world to think towards alternative therapy with less cost and no or little side effects compared to conventional treatments. More research is required for UPFs on the experimental models along with the case controlled studies in order to establish UPFs in the mainstream of treatment.
Keywords: safety